Resistance Patterns of Escherichia coli and Klebsiella pneumoniae Bacteria Against Amikacin, Ceftazidime, Meropenem, Nitrofurantoin Antibiotics in Elderly Patients with UTI in RSUD Dr. Soetomo - Herdiyanti Herdiyanti; Lindawati Alimsardjono; Danti Nur Indiastuti (Juxta: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2019)
Introduction: Urinary tract infection (UTI) is an infection that involves the urinary tract, including the urethra, bladder, ureter, and kidneys. UTI is caused by microorganisms that breed in the urinary tract which are supposed to be free of microorganisms. Two bacterias that cause UTI in general are Escherichia coli and Klebsiella pneumoniae. UTI can occur at any age but generally occurs in the elderly. UTI caused by gram-negative bacteria can be killed with several examples of antibiotics namely amikacin, ceftazidime, meropenem and nitrofurantoin. These antibiotics found resistance to the bacteria that cause the UTI. This research is to determine the resistance patterns of Escherichia coli and Klebsiella pneumoniae bacteria against amikacin, ceftazidime, meropenem, nitrofurantoin antibiotics in elderly patients with UTI in Dr. Soetomo Surabaya January-June 2017 period.